Quasi-periodic oscillations in the long-term radio light curves of the blazar AO 0235+164. Issue 4 (11th January 2021) - Tripathi, Ashutosh; Gupta, Alok C; Aller, Margo F; Wiita, Paul J; Bambi, Cosimo; Aller, Hugh; Gu, Minfeng
ABSTRACT: We present time series analyses of three-decade long radio observations of the BL Lacertae object AO 0235+164 made at the University of Michigan Radio Astronomical Observatory operating at three central frequencies of 4.8, 8.0, and 14.5 GHz. We detected a quasi-periodic oscillation of ∼965 d in all three frequency bands in the light curve of the effectively simultaneous observations, along with strong signals at ∼1950, ∼1350, and ∼660 d. The periodicity is analysed with three methods: data-compensated discrete Fourier transform, generalized Lomb–Scargle periodogram, and Weighted Wavelet Z-transform. These methods are chosen as they have different analysis approaches toward robust measurement of claimed periodicities. The quasi-periodic oscillation at 965 ± 50 d is found to be significant (at least 3.5σ) and is persistent throughout the observation for all three radio frequencies, and the others, which may be harmonics, are comparably significant in at least the 8.0 and 14.5 GHz bands. We briefly discuss plausible explanations for the origin of such long and persistent periodicity.